2016
DOI: 10.1200/jco.2015.64.2322
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Analysis of Oncogenic Driver Mutations and Environmental Factors: Japan Molecular Epidemiology for Lung Cancer Study

Abstract: The mutational spectrum is associated with smoking, body mass index, and other environmental factors, as well as with ERβ expression. Little association was observed between HPV and NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 27 publications
5
70
0
2
Order By: Relevance
“…2). The rate of false positive droplet events did not depend on the total amount of DNA (data not shown, Taly et al, 2013, Kawaguchi et al, 2016). Therefore, the LOB was determined by evaluating the 95% one-tailed upper limit of the model distribution, as done in previous reports (Taly et al, 2013, Kawaguchi et al, 2016).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…2). The rate of false positive droplet events did not depend on the total amount of DNA (data not shown, Taly et al, 2013, Kawaguchi et al, 2016). Therefore, the LOB was determined by evaluating the 95% one-tailed upper limit of the model distribution, as done in previous reports (Taly et al, 2013, Kawaguchi et al, 2016).…”
Section: Resultsmentioning
confidence: 85%
“…We used this test system to assess multiplex detection of 3 EGFR mutations in 45 samples of surgically resected primary tumors from NSCLC patients enrolled in the Japan Molecular Epidemiology for Lung Cancer Cases (JME) study (Kawaguchi et al, 2016). That study (UMIN000008177) is a prospective, multicenter molecular epidemiological analysis designed to address associations between driver mutations and smoking and other environmental factors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, oncogenic driver mutations, which serve as the basis for precision therapy for lung cancer, are not well characterized by smoking status. A recent prospective study with a mix of smoking and non-smoking Asians identified some key differences in these patients’ mutation profiles (38), but much additional work is needed including prospective studies of populations with ethnic heterogeneity and variation in smoking behaviors. Breast cancer is a screening detectable cancer, but effective intervention requires access and use of healthcare, which has been found to be heterogonous across Asian subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…The specific EGFR mutations driving much of the sensitivity to tyrosine kinase inhibition (TKI) were first identified in 2004 following a subgroup analysis of patients who showed tumor responsiveness during treatment with a TKI [30,31]. The EGFR mutation is most common in non-smoking Asian females with adenocarcinoma, though it is frequently found outside of this demographic [31, 68,69]. While the EGFR mutation has also been found in other types of NSCLC, it is most frequently associated with adenocarcinoma [70].…”
Section: Mutation and Gene Fusion Analysismentioning
confidence: 99%